Ortho‐Stabilized 18F‐Azido Click Agents and their Application in PET Imaging with Single‐Stranded DNA Aptamers. Issue 43 (20th August 2015) - Wang, Lu; Jacobson, Orit; Avdic, Din; Rotstein, Benjamin H.; Weiss, Ido D.; Collier, Lee; Chen, Xiaoyuan; Vasdev, Neil; Liang, Steven H.
Abstract Azido 18F‐arenes are important and versatile building blocks for the radiolabeling of biomolecules via Huisgen cycloaddition ("click chemistry") for positron emission tomography (PET). However, routine access to such clickable agents is challenged by inefficient and/or poorly defined multistep radiochemical approaches. A high‐yielding direct radiofluorination for azido 18F‐arenes was achieved through the development of an ortho‐oxygen‐stabilized iodonium derivative (OID). This OID strategy addresses an unmet need for a reliable azido 18F‐arene clickable agent for bioconjugation reactions. A ssDNA aptamer was radiolabeled with this agent and visualized in a xenograft mouse model of human colon cancer by PET, which demonstrates that this OID approach is a convenient and highly efficient way of labeling and tracking biomolecules.